Validation of automated apparatus for upper limb velocity testing - Leandro Medeiros Silva; Felipe José Aidar; Dihogo Gama Matos; Eduardo Estevan Santana; Matheus Peixoto Dantas; Petrus Gantois Santos; Paulo Moreira Dantas; Breno Araújo Cabral (Desafio Singular, 2018)
The purpose of this paper was to validate the ability of automated devices to measure the velocity of the upper limbs. Thus, 144 students, from 8 to 17 years old, both sexes, participated in the study in a social project in the city of Natal/RN. The Automated Tapping Test (AATT) was developed following the dimensions of the original EUROFIT test, but built out of metal parts, so that the calibration was more accurate and could be read as an electronic signal by the integrated circuit. The upper limb velocity test was applied in three steps: before performing the original test, all participants underwent a laterality check and then motor practice similar to the original test. After 30 minutes, the first step in the pattern established by the EUROFIT test battery was performed and 30 minutes later, the third stage, with the AATT. The measurement reliability of the automated apparatus was tested through intraclass correlations and a strong intraclass interaction coefficient of r = 0.901 was found. In conclusion, the AATT was found to be accurate and efficient as to what it is proposed to evaluate, being able to minimize the intra-evaluator error and to assist professionals in the sports.